A relational analysis of enterprise obligations and carbon majors for climate justice - Sara L. Seck (Oñati Socio-Legal Series)
A coherent theory of climate justice must answer the question of “who owes what to whom, and why?” This paper considers the human rights responsibilities of business enterprises for climate injustice. I first introduce a relational approach to legal analysis, drawing upon the work of diverse theorists who confront the dominant yet unacknowledged prevalence of the bounded autonomous individual of liberal thought in diverse areas of law and policy, and offer a method for reinterpretation and transformation of law in the Anthropocene. I then examine the 2018 Principles on Climate Obligations of Enterprises, drafted by a sub-group of the legal experts responsible for the 2015 Oslo Principles. Ultimately, I argue that a coherent theory of justice in the Anthropocene is dependent upon relational insights which enable us to tell old stories in new ways, and so reveal the interconnectedness and interdependence of all beings, while accounting for power and difference.